Tilapia in Ecuador - Jácome, Janeth (2019)
Tilapia is a freshwater fish native to Africa that has many characteristics that make it an excellent fish for aquaculture, but it is also considered one of the most dangerous invasive exotic species in the world due to its adaptability and reproductive potential. This essay analyzes the dilemma between the benefits of these fish as an alternative to contribute to agrifood security and the threat it poses to Ecuador's aquatic biodiversity. The absence of official information makes it necessary to investigate the effect of the invasions by tilapia in the rivers, lagoons and estuaries colonized by this species. The level of action to prevent, eradicate or control the tilapia in Ecuador has been very limited and therefore the need to establish strategies to prevent its spread to areas not yet invaded is imposed. Although the government of Ecuador has regulations that restrict the introduction of exotic species, the reality is that, in the case of the tilapia, far from establishing adequate controls, the culture of these fish is promoted without major objections. The possibility of adopting biocontrol strategies to eradicate and / or mitigate the consequences of the invasion by tilapia in the country and the need to promote educational campaigns to create a new environmental behavior, conscience and responsibility in society is discussed.